Estimation of Profunda Artery Perforator Flap Weight Using Preoperative Computed Tomography Angiography - Greige, Nicolas; Nash, David; Salibian, Ara A.; Sultan, Steven M.; Ricci, Joseph A.; Thanik, Vishal D.; Weichman, Katie E. (Journal of Reconstructive Microsurgery, 2020)
Background Given the relatively small size of thigh-based flaps and the possible necessity for a multiflap reconstruction, it is imperative to arrive at an accurate estimation of flap weight during preoperative planning. It was our objective to develop a novel technique for the preoperative estimation of profunda artery perforator (PAP) flap weight.Methods All patients that underwent transverse PAP flap breast reconstruction at two institutions were retrospectively reviewed. Subcutaneous tissue thicknesses were measured on axial computed tomography angiography scans at several predetermined points. The distance from the inferior gluteal crease to the PAP was also recorded. Linear regression was used to estimate flap weight.Results A total of 18 patients (32 flaps) were analyzed. The median intraoperative flap weight was 299 g (interquartile range [IQR]: 235–408). The parsimonious model (R2 = 0.80) estimated flap weight using the Eq. 77.9x + 33.8y + 43.4z – 254.3, where x is subcutaneous tissue thickness (cm) at the lateral border of long head of the biceps femoris at a level 4.5 cm caudal to the inferior gluteal fold, y is distance (cm) from the inferior gluteal fold to the dominant PAP, and z has a value of 1 if the patient was scanned in the supine position or 0 if prone. The aforementioned formula yielded a median estimated flap weight of 305 g (IQR: 234–402) and a median percent error of 10.5% (IQR: 6.1–16.2).Conclusion The authors demonstrate a simple and accurate formula for the preoperative estimation of transverse PAP flap weight for breast reconstruction.
Keywords: PAP flap; flap weight estimation; predictive model